2004
DOI: 10.1093/pcp/pch060
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Targets Elongating Cells by Reducing Cell Wall Extensibility in Wheat Roots

Abstract: Phytotoxicity of aluminum is characterized by a rapid inhibition of root elongation at micromolar concentrations, however, the mechanisms primarily responsible for this response are not well understood. We investigated the effect of Al on the viscosity and elasticity parameters of root cell wall by a creep-extension analysis in two cultivars of wheat (Triticum aestivum L.) differing in Al resistance. The root elongation and both viscous and elastic extensibility of cell wall of the root apices were hardly affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
154
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(163 citation statements)
references
References 24 publications
6
154
0
3
Order By: Relevance
“…It has been suggested that the swollen and distorted root tip cells under Al stress are due, at least in part, to disruption of the cell wall structure, integrity, and function (SI Appendix, Fig. S6) (32)(33)(34). Therefore, limiting the accumulation of toxic Al 3+ in the root tip cell wall could help mitigate Al toxicity in plants.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the swollen and distorted root tip cells under Al stress are due, at least in part, to disruption of the cell wall structure, integrity, and function (SI Appendix, Fig. S6) (32)(33)(34). Therefore, limiting the accumulation of toxic Al 3+ in the root tip cell wall could help mitigate Al toxicity in plants.…”
Section: Discussionmentioning
confidence: 99%
“…The cell wall is a major target for Al accumulation and Al toxicity in higher plants (23,24). The root, and more specifically, the root tip, is the primary site of Al toxicity, and the majority (∼90%) of the root Al resides in the cell wall (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Horst (1995) reported that aluminum bound to cell wall components increases wall rigidity, affects cell wall loosening, and thus ultimately inhibits root elongation. Ma et al (2004) demonstrated that aluminum decreases cell wall viscosity and elasticity, thus reducing cell wall extensibility, and, as a consequence, cell elongation is inhibited. Therefore, higher aluminum sensitivity is correlated with more aluminum accumulation in the cell wall, as demonstrated in maize (Zea mays) suspension cells (Schmohl and Horst, 2000) and intact root apices (Eticha et al, 2005a), rice , triticale (Liu et al, 2008), and rice bean (Vigna umbellata; Zhou et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The cell wall is very complex in structure and composition. The binding of aluminum changes cell wall structure, makes the wall more rigid, and reduces mechanical extensibility and cell expansion (Tabuchi and Matsumoto, 2001;Ma et al, 2004). An aluminum-sensitive rice cultivar accumulates higher aluminum in the cell wall than an aluminum-resistant cultivar .…”
mentioning
confidence: 99%